A Human Resource Perspective and Proposition on Technology and Development - V Basil Hans (Journal of Advanced Research in Economics and Business Management, 2025)
The rapid pace of technical innovation has changed the way global development works, making human resources a key factor in long-term progress. This article examines the complex interplay between technology and human resource development, highlighting the ways in which digital transformation alters skills, organisational frameworks, and worker expectations. It looks into how technology may both boost productivity and change the way people work. The study emphasises the significance of strategic human resource policies that promote adaptation, ongoing learning, and innovation, utilising interdisciplinary viewpoints. It also looks at how growing human capital affects how fairly technical advantages are shared across developing and industrialised nations. The study ends by suggesting a framework that brings together technology innovation and human-centered development techniques. This will make sure that the future of work is still open to everyone, strong, and able to meet the requirements of society.